Evaluation of the effectiveness of almond and castor seed oil demulsifiers for emulsion treatment - Kinate, Bright Bariakpoa; Okoroma, Jeremiah Ifeanyi; Abu, Robin Nyemenim; Vincent, Jonathan Lewuga (International Journal of Chemical and Process Engineering Research, 2026)
Water production alongside crude oil almost always leads to emulsion formation, which poses serious challenges during production, transportation, and refining. These emulsions are often very stable and must be separated efficiently to ensure smooth operations and reduce costs. Chemical demulsification is the most common treatment method, but the use of synthetic chemicals raises environmental and economic concerns. This study investigates the efficiency of almond seed oil (AMSO) and castor seed oil (CSO) demulsifiers and compares them with the xylene demulsifier for crude oil emulsion treatment. Bottle tests were carried out using crude oil emulsions mixed with each demulsifier at ratios of 95:5, 90:10, 85:15, 80:20, and 75:25 (emulsion to demulsifier). The mixtures were stirred, agitated, and heated at different temperatures (28 °C, 40 °C, 60 °C, and 80 °C), and water separation was monitored over a 300-minute period at 30-minute intervals. The results showed that water separation improved with AMSO and CSO demulsifiers at higher dosages and longer separation times. Xylene remained the most effective demulsifier across all conditions, especially at elevated temperatures. However, CSO consistently outperformed AMSO, proving more responsive to both temperature and concentration. AMSO, while less effective, improved at higher dosages and at 80 °C. While xylene demulsifier remains the most efficient, CSO demulsifier shows real promise as a greener alternative. With further optimization, natural seed oils could provide a sustainable pathway for reducing dependence on synthetic demulsifiers in crude oil processing.